Analysis of potential critical equipment and technical system on a modern PSV. Recommending a method for Troms Offshore Management AS - Løvmo, Signy Anita (UiT The Arctic University of Norway, 2016)
This thesis is a part of a master’s degree in Technology and Safety in the High North at the University of Tromsø- The Arctic University of Norway. The thesis has been written during the spring semester of 2016. Safety is a large part of maritime operations and all tools to improve safety and reliability is considered. Even in these days when economy in the oil related industry is worse than ever. The International Maritime Organization (IMO) ensures that all suppliers and contractors are obliged to follow rules and regulations in order to ensure a safe workplace for all members the industry and protection of the environment all over the globe. One of those regulations is the International Code for Safe Operations of Ships and Pollution Prevention (International Safety Management (ISM) Code) paragraph 10.3: “The company should identify equipment and technical systems the sudden operational failure of which may result in hazardous situations. The SMS should provide for specific measures aimed at promoting the reliability of such equipment or systems. These measures should include the regular testing of stand-by arrangements and equipment or technical systems that are not in continuous use.“ The subject of the thesis is “Analysis of potential critical equipment and technical systems on a modern PSV- Recommending a method for Troms Offshore Management AS”. The thesis will look at several methods that may be used to comply with the ISM Code 10.3. These methods is tested on an equipment or technical system that is used on a vessel in the Troms Offshore fleet, whereas those tests was presented to two expert panels in order to obtain information on how these methods are interpreted and found usable in practice. The method that is most suited in regards to being able to perform for all equipment and technical systems, being understandable for the intended readers, being constructed in a way that everyone can achieve the same result and being able to express enough information that everyone can access the reason for why ...